Ponding system for palm oil mill effluent treatment [in Malaysia] - Chooi, C.F. (IPMKSM, 2013)
This paper reviewed the ponding system for palm oil mill effluent (POME) treatment. The oldest plant had been in use since July 1979, results over the last five years, had fortified the view that ponding system was stable and reliable but requiring pond management with regards to anaerobic sludge build-up. Anaerobic sludge solids build-up in the ponding system had to be accepted as a feature of anaerobic digestion of POME. The problem had been tackled by dewatering in sandbeds and lately field application of the sludge was being tried out to gain experience. The performance of the ponding system to date points to it, being a viable, low cost and effective method for treatment of POME